Agranulocitoza in makulopapulozni izpuščaj po zdravljenju s tiklopidinom - prikaz primera - Blatnik, Janja (Zdravniški vestnik, 2003)
Background. Ticlopidine is one of inhibitors of platelet aggregation indicatedfor reducing the risk of thrombotic stroke in patients who have experienced thrombotic stroke, ischemic attacks, unstable angina pectoris, coronary artery stenting and peripheral vascular bypass grafting. The weak point of this treatment are many serious adverse effects, the most serious of them being neutropenia. Patient and therapy. We report a case of a 70-years old woman who developed agranulocytosis and skin rash by the end of the 4-weektherapy with ticlopidine. After discontinued therapy with ticlopidine and when lenograstim was administered, agranulocytosis, anemia and rash subsided in one week. Conclusions. As ticlopidine is associated with serious complications, its application has to be reserved for those patients who are intolerant to aspirin therapy.
Keywords: Adverse Effects; Agranulocitoza; Agranulocytosis; drug; Eksantem; Exanthema; kožne spremembe; nevtropenija; Therapeutic Use; Ticlopidine; Tiklopidin; zdravila